Ideologi Gerakan Muhammadiyah - Muhammad Arman; Ayu Andriani; M. Amin (CV. ITTC INDONESIA, 2026)
This study aims to analyze the ideology of the Muhammadiyah movement as a normative and operational foundation in conducting da‘wah, social activities, and organizational management amid the dynamics of modern society. This research employs a qualitative approach using library research. The findings indicate that the ideology of the Muhammadiyah movement is rooted in the principles of tawhid, amar ma‘ruf nahi munkar, and tajdid, which affirm Muhammadiyah’s character as a modernist and progressive Islamic movement. This ideology is not merely normative in nature but also functions as a practical framework for the development of charitable enterprises in the fields of education, health, social services, and community empowerment. Furthermore, Muhammadiyah’s ideology is dynamic and adaptive to contemporary challenges, including globalization, value disruption, and technological advancement. However, the study also identifies challenges in the internalization of ideology, particularly related to cadre formation and the strengthening of ideological commitment at the grassroots level. Therefore, the reinforcement and revitalization of Muhammadiyah’s ideology through sustainable cadre development are considered strategic necessities to ensure the continuity and relevance of the movement in the future.